Partilhas do documentário : a experiência na realização de Bateia - Giacomini, Jair Marcos (2016)
The subject of this thesis is the process of making a documentary, titled Bateia, directed by the own author of this academic work. The proposal for produce the film aims to promote, from a practice, the understanding of matters that orbit the documentary cinema. To guide the procedures of the documentary realization and the reflection/writing of the thesis, an open methodology was developed. Named in process, the methodology has as its basic premise the view that the path setting is not determined a priori manner; rather, it is the process experienced by the subject-documentarist-researcher who brings out the questions to be articulated in the study. The main concepts covered in the study are: distribution of the sensible, staging, risk of the real and decisão-tomada. The discussion of these issues is strengthened by the fact that the subjects filmed in the documentary are members of a theater group – Companhia de Teatro Íntimo – whose working method involves procedures and similar conceptions to this academic research, such as: relate theory and practice, the idea of risk as his perspective and principles of sharing as form to act.In order to articulate the experience of the production of Bateia with the theoretical concepts are invited authors from academy and also documentarists: on the first field, Jacques Rancière, David Bordwell, Fernão Ramos and Jean-Louis Comolli; from the side of the directors, Robert Flaherty, Dziga Vertov, Frederick Wiseman and Jean Rouch. That procedure, in line with the general purpose of the thesis, seeks to intensify the relationship between the practice of making documentary and the reflection on that. The thesis points to the productivity of the relationship between the subject-of-the-camera and filmed people built in the interval space of sharings. It also proposes "decisão-tomada" as a theoretical concept to promote the reflection on the documentary realization from the director's experience.